Appreciation for Journal of Medical Toxicology (JMT) 2025 Peer Reviewers - Howard A. Greller; Mark B. Mycyk (Journal of Medical Toxicology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

An Outbreak of Synthetic Cannabinoid-Adulterated Tianeptine Products in New Jersey – Case Series - Christopher J. Counts; Anthony V. Spadaro; Trevor A. Cerbini; Alex J. Krotulski; Sara E. Walton; Howard A. Greller; Lewis S. Nelson; Bruce E. Ruck; Oliver Hung; Barry Logan; Diane P. Calello (Journal of Medical Toxicology, 2025)
Background Tianeptine, an atypical antidepressant not approved in the United States, is readily purchased from unregulated markets such as the internet and gas stations. We became aware of a cluster of 34 patients in New Jersey who became ill following ingestion of the tianeptine containing-product Neptune’s Fix, the rate of which (4.6 cases per month) far exceeded the background rate for this substance of 0.5 cases per year. Methods We retrospectively identified tianeptine exposures reported to the New Jersey Poison Information and Education System (NJPIES) prior to June 2023 to determine the background rate of tianeptine exposure. From June 2023– February 2024 we prospectively surveilled tianeptine exposures reported to NJPIES, recorded demographic and clinical information, and recruited samples for testing. Six samples of the ingested products were obtained and analyzed using gas chromatography mass spectrometry (GC-MS) and liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QTOF-MS). Whole blood samples from two patients were tested for tianeptine and synthetic cannabinoids. Results During the period of interest, NJPIES received 41 exposure calls, with 37 reporting acute toxicity in 34 unique patients, two reporting chronic tianeptine use, and two reporting withdrawal. Among the 37 exposures resulting in acute toxicity, commonly reported effects included altered mental status, tachycardia, hypotension, and seizures. 43% ( n = 16) were intubated, and 65% ( n = 24) were admitted to the ICU. Analytical testing of six samples identified variable product composition, containing various xenobiotics including tianeptine, kava alkaloids, natural cannabinoids, and the synthetic cannabinoids MDMB-4en-PINACA and ADB-4en-PINACA. MDMB-4en-PINACA was detected in one of the two patient blood specimens. Conclusions These cases represent a marked increase in tianeptine exposures compared with the poison center’s historical average. Analytical testing revealed variable product composition, including the presence of synthetic cannabinoids. Clinicians should be aware that tianeptine containing products are widely available, unregulated, and can be adulterated.

Excellence in Review—Appreciation for Journal of Medical Toxicology’s 2024 Peer Reviewers - Howard A. Greller; Mark B. Mycyk (Journal of Medical Toxicology, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Attempted Self-Harm with Elemental Thallium Purchased Online: Case Report with Analytical Confirmation - Anthony Spadaro; Andrew Sae Young Lee; Hilda Pineda; Bruce Ruck; Diane P. Calello; Howard A. Greller; Lewis S. Nelson; Mehruba A. Parris (Journal of Medical Toxicology, 2024)
Introduction Thallium is a highly toxic metal, with most publications demonstrating poisoning from thallium salts. We report on a patient with elevated serum and urine thallium concentrations from an intentional ingestion of elemental thallium purchased from the internet for self-harm. Case Report The regional poison center was contacted about an 18-year-old man who ingested a fragment from a 100-gram bar reported to be elemental thallium. Serial serum and urine thallium concentrations were obtained. Prussian blue was started on hospital day (HD) 2. A metal fragment was seen on abdominal x-ray and removed via colonoscopy on HD3. The ingested fragment was analyzed via inductively coupled plasma mass spectrometry (ICP-MS) and found to be 87.0% elemental thallium. The initial serum thallium concentration obtained on HD1 was 423.5 mcg/L (reference range < 5.1 mcg/L), which subsequently decreased to 4.5 mcg/L, 29 days after the ingestion. An initial random urine thallium concentration obtained on HD 3 was 1850.5 mcg/g creatinine (reference range < 0.4 mcg/g creatinine). The patient remained hospitalized for 23 days and, when seen in follow-up, had not developed any signs or symptoms of thallium toxicity. Discussion Elemental thallium ingestion is a rare toxicologic exposure, with limited published clinical and analytical experience to guide management. This case report describes a patient with ingestion of elemental thallium who developed elevated serum and urine thallium concentrations and was treated with Prussian blue. Despite having elevated serum and urine thallium concentrations consistent with previous fatal exposures, more evidence is needed to understand the differences between elemental thallium and thallium salts.

Appreciation and Gratitude to Journal of Medical Toxicology (JMT) Peer Reviewers in 2023 - Howard A. Greller; Mark B. Mycyk (Journal of Medical Toxicology, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

ACMT Position Statement: End the Use of the Term “Excited Delirium” - Andrew I. Stolbach; Paul I. Dargan; Howard A. Greller; Richard J. Hamilton; Kelly Johnson-Arbor; Brian Patrick Murray; Daniel Ovakim; Laura Tormoehlen; Lewis S. Nelson; Sukhshant Atti; Jeffrey N. Bernstein; Caitlin Bonney; et al. (Journal of Medical Toxicology, 2023)

The Journal of Medical Toxicology: Our Once and Future Journal - Howard A. Greller; Peter R. Chai; Natalie R. Neumann; Mark B. Mycyk (Journal of Medical Toxicology, 2022)

Medical Toxicology and COVID-19: Our Role in a Pandemic - Natalie R. Neumann; Peter R. Chai; David M. Wood; Howard A. Greller; Mark B. Mycyk (Journal of Medical Toxicology, 2020)

Buprenorphine Initiation in the Emergency Department: a Thematic Content Analysis of a #firesidetox Tweetchat - Megan Chenworth; Jeanmarie Perrone; Jennifer S. Love; Howard A. Greller; Abeed Sarker; Peter R. Chai (Journal of Medical Toxicology, 2020)

The Virtual Toxicology Journal Club: the Dissemination and Discussion of Noteworthy Manuscripts Using Twitter - Peter R. Chai; Anne-Michelle Ruha; Kelly E. Wong; Derek L. Monette; Meghan B. Spyres; Jeff Lapoint; Howard Greller; Mark B. Mycyk (Journal of Medical Toxicology, 2018)

A Review of the Toxicologic Implications of Obesity - Matthew Zuckerman; Howard A Greller; Kavita M Babu (Journal of Medical Toxicology, 2015)

Case Series: Inhaled Coral Vapor—Toxicity in a Tank - Payal Sud; Mark K. Su; Howard A. Greller; Nima Majlesi; Amit Gupta (Journal of Medical Toxicology, 2013)